1996
DOI: 10.1175/1520-0477(1996)077<2007:tafros>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Antarctic First Regional Observing Study of the Troposphere (FROST) Project

Abstract: An account is given of the Antarctic First Regional Observing Study of the Troposphere (FROST) project, which has been organized by the Physics and Chemistry of the Atmosphere Group of the Scientific Committee on Antarctic Research. The goals of FROST are to study the meteorology of the Antarctic, to determine the strengths and weaknesses of operational analyses and forecasts over the continent and in the surrounding ocean areas, and to assess the value of new forms of satellite data that are becoming availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Despite the magnitude differences, the vector directions are in reasonable agreement for all of East Antarctica, particularly for South Pole and along Shackleton Coast, west of the Ross Ice Shelf. Over West Antarctica there is more substantial disagreement in the vector-averaged wind directions (Turner et al 1996). This may be due in part to the South Pacific blocking conditions present during the July SOP, which are not present in the mesoscale model.…”
Section: Initial-hour Comparisons With Observations and Climatologiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite the magnitude differences, the vector directions are in reasonable agreement for all of East Antarctica, particularly for South Pole and along Shackleton Coast, west of the Ross Ice Shelf. Over West Antarctica there is more substantial disagreement in the vector-averaged wind directions (Turner et al 1996). This may be due in part to the South Pacific blocking conditions present during the July SOP, which are not present in the mesoscale model.…”
Section: Initial-hour Comparisons With Observations and Climatologiesmentioning
confidence: 95%
“…# Current affiliation: Department of Aerospace Engineering Sciences, University of Colorado, Boulder, Colorado. national collaboration of the Scientific Committee on Antarctic Research Working Group on Physics and Chemistry of the Atmosphere, with principal goals of examining the performance of operational analyses and forecasts for Antarctica and the surrounding sea-ice zone during three 1-month-long SOPs in July 1994, October-November 1994, and January 1995 (Turner et al 1996). In high southern latitudes, weather data assimilation and prediction face an array of obstacles that limit operational performance, including the scarcity of available data and long-distance communications difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…These factors result in forecasts and analyses that are of poorer quality compared with other parts of the world (Bourke 1996). This problem has been addressed by the international Scientific Committee on Antarctic Research Working Group on Physics and Chemistry of the Atmosphere by advancing the FROST project as a research and data gathering exercise to evaluate the potential for improving the present situation (Bromwich and Smith 1993;Turner et al 1996).…”
Section: W E a T H E R A N D F O R E C A S T I N Gmentioning
confidence: 99%
“…The primary goal of FROST is to examine the performance of operational analyses and forecasts for Antarctica and the surrounding sea ice zone during three 1-month-long special observing periods (SOPs): (a) SOP-1 (winter) during July 1994, (b) SOP-2 (spring) during 15 October-15 November 1994, and (c) SOP-3 (summer) during January 1995 (Bromwich and Smith 1993;Turner et al 1996). The U.S. component of this project is an evaluation of analyses and forecasts produced by NCEP.…”
Section: W E a T H E R A N D F O R E C A S T I N Gmentioning
confidence: 99%
“…Using observations from the Antarctic First Regional Observing Study of the Troposphere (FROST) in 1994-1995, Bromwich and Smith (1993, Turner et al (1996), and Turner et al (1999) found that the NCEP-NCAR and ECMWF reanalysis are able to produce the main circulation features over Antarctica, despite some minor discrepancies in the depths and locations of the lows. Cullather et al (1997) compared the two reanalysis products for a 10-yr (1985-1995) period and found that surface pressure in the two reanalysis datasets is in better agreement with observations than surface air temperature and wind, and that the errors in both reanalysis at the standard pressure levels decrease with time.…”
Section: Introductionmentioning
confidence: 99%